Gagasan Kebangsaan dan Moderatisme K.H. Mas Mansur (1896 – 1946) Dalam Tafsir Langkah Moehammadijah - Kiptiyah, Siti Mariyatul (JURNAL JAWI, 2018)
This paper analyzes the K.H. Mas Mansur’s nationalism and moderation ideas in the Interpretation of Langkah Moehammadijah 1939. As a product of culture and thought, the Qur’anic interpretation always reflects the ideological reasoning of the author. This study will examine the role of the Kyai Mas Mansur in bringing up Indonesianist ideas ahead of independence. The question answered in this paper is the extent of K.H. Mas Mansur’s nationality and moderation ideas in Interpretation of Langkah Moehammadijah? How can these ideas appear in the interpretation? This article shows that in 12 steps Muhammadiyah was initiated by K.H. Mas Mansur, seven of them sought spiritual strengthening and national unity. The seven things are deepening the entry of faith, expanding religious ideology, producing character, guiding the practice of the core of theqad, strengthening unity, upholding justice, and carrying out wisdom. Meanwhile, the next five steps are specifically intended for Persyarikatan Muhammadiyah as a da'wah organization that is encouraged to maintain unity, which is to strengthen the Tanwir Majlis, hold part conferences, deliberate decisions, oversee internal movements, and connect outside movements. These ideas appear to be nothing but related to power relations especially in the capacity of K.H. Mas Mansur as chairman of the Muhammadiyah, a reformer figure, and an Indonesian freedom fighter.